The 12 Weeks General Preparation Phase Exercise Improve Body Composition on Female University Basketball Athletes - Fairuz Puti Asri; Eko Juli Fitrianto; Hermanto; Lilik Herawati (Gladi : Jurnal Ilmu Keolahragaan, 2026)
General Preparation Phase (GPP) exercise is the initial point in training periodisation, focusing on the foundation construction for physical capability, basic technique, and mental preparedness of an athlete prior to entering specialised training period. At this stage, physical exercise was conducted with high volume and moderate intensity intended to raise aerobic capacity and bio motor components in general as part of anatomical adaptation process, preparing the body for a more specific load in accordance with specific sports demand. This experimental study aims to explore the effects of GPP exercise on basketball players’ body composition, consisting of body fat percentage and muscle mass, measured using BIA (Bio-Electric Impedance Analysis), then analysed using paired t-test. Participants for this study were 24 female basketball players from Universitas Negeri Jakarta Varsity Basketball Club who performed GPP for 12 weeks. The result showed there was a 7.70% decrease in body fat percentage, and an increase of 4.42% in muscle mass after GPP of training. It can be concluded that practising GPP has an impact on body fat percentage and muscle mass of the subjects